A novel repeat sequence-based PCR (rep-PCR) using specific repeat sequences of Mycobacterium intracellulare as a DNA fingerprinting - Shin, Jeong-Ih; Ha, Jong-Hun; Kim, Kyu-Min; Choi, Jeong-Gyu; Park, Seo-Rin; Park, Hyun-Eui; Park, Jin-Sik; Byun, Jung-Hyun; Jung, Myunghwan; Baik, Seung-Chul; Lee, Woo-Kon; Kang, Hyung-Lyun; et al. (Frontiers in Microbiology, 2023)
Repetitive sequence-based PCR (rep-PCR) is a potential epidemiological technique that can provide high-throughput genotype fingerprints of heterogeneous Mycobacterium strains rapidly. Previously published rep-PCR primers, which are based on nucleotide sequences of Gram-negative bacteria may have low specificity for mycobacteria. Moreover, it was difficult to ensure the continuity of the study after the commercial rep-PCR kit was discontinued. Here, we designed a novel rep-PCR for M. intracellulare, a major cause of nontuberculous mycobacterial pulmonary disease with frequent recurrence. We screened the 7,645 repeat sequences for 200 fragments from the genome of M. intracellulare ATCC 13950 in silico, finally generating five primers with more than 90% identity for a total of 226 loci in the genome. The five primers could make different band patterns depending on the genome of three different M. intracellulare strains using an in silico test. The novel rep-PCR with the five primers was conducted using 34 bacterial samples of 7 species containing 25 M. intracellulare clinical isolates, compared with previous published rep-PCRs. This shows distinguished patterns depending on species and blotting assay for 6 species implied the sequence specificity of the five primers. The Designed rep-PCR had a 95-98% of similarity value in the reproducibility test and showed 7 groups of fingerprints in M. intracellulare strains. Designed rep-PCR had a correlation value of 0.814 with VNTR, reference epidemiological method. This study provides a promising genotype fingerprinting method for tracing the recurrence of heterogeneous M. intracellulare.